A strategic approach to multimodal discourse analysis - Menendez, Salvio Martin (2015)
In the paper the author argues that multimodal discourse analysis examines the traditional issues of rhetoric from a pragmatic-discursive perspective and therefore may be regarded as a part of rhetoric. Starting from systemic-functional linguistics, the author proposes a method for studying the multimodality of discourse which highlights the notion of strategy, defi ned as a plan for achieving a particular purpose.